2012
DOI: 10.1002/nbm.2790
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of flow‐sensitive alternating inversion recovery (FAIR) for perfusion functional MRI of rodent brain

Abstract: Arterial spin labeling (ASL) MRI provides a noninvasive method to image perfusion, and has been applied to map neural activation in the brain. Although pulsed labeling methods have been widely used in humans, continuous ASL with a dedicated neck labeling coil is still the preferred method in rodent brain functional MRI (fMRI) to maximize the sensitivity and allow multislice acquisition. However, the additional hardware is not readily available and hence its application is limited. In this study, flow-sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…The more rapid fall in the glucoCEST signal compared with the 2DG6P signal in 31 P MRS spectra can be ascribed to several factors, including the sensitivity to detection, anesthesia and further metabolism of 2DG6P. First, the more rapid decrease to baseline compared with that reported in the 13 C MRS literature 8 may be due to restricted in vivo sensitivity of glucoCEST in our experiments; specifically, the glucoCEST signal arises from exchange of protons on the 2DG and 2DG6P molecules with that on water, and this rate is sensitive to the molecular environment including pH, temperature, and the presence of other solutes. Unlike the in vitro conditions, the presence of other solutes in vivo will alter the -OH exchange properties and hence the CEST signal.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The more rapid fall in the glucoCEST signal compared with the 2DG6P signal in 31 P MRS spectra can be ascribed to several factors, including the sensitivity to detection, anesthesia and further metabolism of 2DG6P. First, the more rapid decrease to baseline compared with that reported in the 13 C MRS literature 8 may be due to restricted in vivo sensitivity of glucoCEST in our experiments; specifically, the glucoCEST signal arises from exchange of protons on the 2DG and 2DG6P molecules with that on water, and this rate is sensitive to the molecular environment including pH, temperature, and the presence of other solutes. Unlike the in vitro conditions, the presence of other solutes in vivo will alter the -OH exchange properties and hence the CEST signal.…”
Section: Discussionmentioning
confidence: 96%
“…Unlike the in vitro conditions, the presence of other solutes in vivo will alter the -OH exchange properties and hence the CEST signal. To better determine the amount of 2DG6P, we also conducted high-resolution 13 C spectroscopy in brain extracts at several time points after 2DG injection. In the preliminary experiment (data not shown), we found a very high amount of 13 C-2DG6P at 50 minutes, which decreased to near the level of 5 minutes at 80 minutes after 2DG injection, which suggested that the 2DG6P may decrease faster than that measured by 31P MRS. We also observed a new peak at B184.2 p.p.m.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations